Relación entre los créditos y depósitos de las bancas múltiples con las cajas municipales de ahorro y crédito en Loreto, 2017 – 2023 - Del Aguila Garcia, Marianita (2025)
The purpose of this research was to identify the relationship between loans and deposits in Multiple Banks and Municipal Savings and Credit Banks in the Loreto region during the period 2017 - 2023. With a quantitative, descriptive, and non-experimental approach, 84 observations were evaluated for each variable, using official data from INEI and BCRP and applying statistical techniques such as Pearson’s correlation coefficient and the adjusted R². Our theoretical framework included the Financial Intermediation Theory, the Independence and Imperfections Theory, and the Trade-Off Theory, which helped explain the behavior of financial institutions, highlighting the impact of information asymmetry, market imperfections, and the balance between tax benefits and financing costs in the management of loans and deposits. The findings revealed a strong correlation between loans and deposits, with values of 0.7 for Multiple Banks and 0.8 for Municipal Banks. However, the analysis of the adjusted R² (0.6047 and 0.650, respectively) suggests that there are other external factors not considered that influence the behavior of these variables.